2015
DOI: 10.1016/j.ebcr.2015.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Focal frontal epileptiform discharges in a patient with eyelid myoclonia and absence seizures

Abstract: Eyelid myoclonia with absences is classified as a unique type of generalized seizure. Its pathogenesis is proposed to involve the functional abnormalities in cortical–subcortical networks. Here, we describe the case of a 7-year-old boy who had eyelid myoclonia with absences, along with focal motor seizures. Video-EEG monitoring demonstrated eyelid myoclonia associated with 4- to 5-Hz generalized polyspike–waves preceded by focal frontal discharges. Interictal EEG showed focal epileptiform discharges over the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…The ED originating from one of these areas spread to other brain regions through either the transcortical or thalamocortical pathways to project the generalized discharges. This also supports the idea of frontal lobe or occipital lobe‐ originated system epilepsies, which is compatible with the notion of a continuum, rather than a distinction between focal and generalized epilepsies (Wang et al ., 2014; Nar Senol et al ., 2015; Takahashi et al ., 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ED originating from one of these areas spread to other brain regions through either the transcortical or thalamocortical pathways to project the generalized discharges. This also supports the idea of frontal lobe or occipital lobe‐ originated system epilepsies, which is compatible with the notion of a continuum, rather than a distinction between focal and generalized epilepsies (Wang et al ., 2014; Nar Senol et al ., 2015; Takahashi et al ., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that there is an overlap among the types of IGE, and that these epileptic syndromes are not static, but rather dynamic syndromes that evolve into one another over time with a possible continuum mediated by a common genetic abnormality. Thus, it seems more logical to consider JS as a system epilepsy with a high susceptibility to changes in the brain network (Wang et al, 2014;Nar Senol et al, 2015;Takahashi et al, 2015). Photosensitivity is accepted as the main feature of JS (Gülen Abanoz et al, 2018).…”
Section: Diagnostic Pitfalls Of Jeavons Syndromementioning
confidence: 99%
“…The base model used to generate SpW in the present work generated frequencies of events similar to those seen clinically for atypical absences and some manifestations of focal epilepsies ( Blumenfeld 2005 ; Takahashi et al 2015 ). Building on this baseline of stereotyped, single spike per SpW discharges, we have shown that different pathologies linked to genetic risk factors (enhanced NMDA conductance, reduced GABA A receptor-mediated synaptic inhibition) generated multiple spikes per SpW with different spatiotemporal dynamic properties.…”
Section: Discussionmentioning
confidence: 99%
“…It is thought they form part of a continuum of pathologies ranging from benign partial epilepsies through to continuous SpW associated with sleep ( Medeiros et al 2010 ). SpW are also seen in focal epilepsies, particularly (though not exclusively) in extratemporal areas such as frontal, parietal, and occipital cortices ( Takahashi et al 2015 ; Taylor et al 2003 ; Westmoreland 1998 ).…”
Section: Introductionmentioning
confidence: 99%
“…Uważa się, że punkt spustowy napadu znajduje się w korze czołowej lub potylicznej. Impuls wywodzący się z jednego z tych płatów rozprzestrzenia się do innych obszarów mózgu poprzez szlaki transkorowe lub wzgórzowo-korowe, przekształcając się z napadu częściowego w napad uogólniony [16,30,31].…”
Section: Patofizjologia/patomechanizmunclassified